2008
DOI: 10.1021/ie071397j
|View full text |Cite
|
Sign up to set email alerts
|

Cubic Two-State Equation of State for Associating Fluids

Abstract: The Kontogeorgis' approach (CPA; Ind. Eng. Chem. Res. 1996, 35, 4310) was employed for the extension of the Soave-Redlich-Kwong (SRK) equation to associating systems. The two-state association model (TSAM) of Cerdeirin ˜a et al. (J. Chem. Phys. 2004, 120, 6648) was modified and employed for describing the association contribution. The modification of TSAM consisted of developing an expression for the association contribution for the Helmholtz free energy as an explicit function of temperature and density, on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
17
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 33 publications
2
17
0
Order By: Relevance
“…Also, in this work, for reduction of the adjustable parameters of pure ionic liquids, the association energy parameter for pure ionic liquids is fixed to 2600 K and therefore four parameters are adjusted for PR-TS model. This value is obtained from the correlated results using the five-parameter PR-TS EoS that show the association energy parameter is very close to 2600 K, which is consistent with the typical value of association energy parameter reported in the literature [3,38].…”
Section: Pure Componentssupporting
confidence: 82%
“…Also, in this work, for reduction of the adjustable parameters of pure ionic liquids, the association energy parameter for pure ionic liquids is fixed to 2600 K and therefore four parameters are adjusted for PR-TS model. This value is obtained from the correlated results using the five-parameter PR-TS EoS that show the association energy parameter is very close to 2600 K, which is consistent with the typical value of association energy parameter reported in the literature [3,38].…”
Section: Pure Componentssupporting
confidence: 82%
“…The CTS (Cubic Two-State) equation is derived from a combination of two contributions to the Helmholtz energy of a system: a physical part given by the Soave-Redlich-Kwong EoS and a molecular associative term obtained from the Two-State Association model [13]. Its pressure-explicit form is:…”
Section: The Cts Equation Of Statementioning
confidence: 99%
“…Values for Tci, pci and ωi were taken from the Aspen Plus V8.8 database. For self-associating substances, such as water, the physical and association parameters were taken from Medeiros and Téllez-Arredondo [13], who obtained them by fitting the CTS model to measured pressures and densities at saturation conditions. They also showed that the parameters a0i and bi have a similar interpretation to the van der Waals' parameters for non-polar molecules, with a0i being related to intermolecular dispersion energy and bi to the molecular volume.…”
Section: The Cts Equation Of Statementioning
confidence: 99%
See 1 more Smart Citation
“…Recently, Medeiros and Téllez-Arredondo have presented an EoS that can deal with the association of substances, namely, the cubic two-state (CTS) EoS [10]. Its basis is the combination of the Soave-Redlich-Kwong (SRK) EoS, representing the physical part, and the two-state association model for the hydrogen bonding contribution.…”
Section: Introductionmentioning
confidence: 99%